From Classroom to Culture: Islamic Education Teachers’ Strategies for Preserving Local Wisdom in The Digital Era - Utin Darma Ranti; Syamsul Kurniawan (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2026)
This study examines strategies used by Islamic Religious Education (PAI) teachers to preserve local wisdom in the digital-hyperreal era, where virtual cultural representations increasingly shape younger generations’ experiences. Unlike previous research focusing mainly on integrating local culture into teaching practices, this study positions PAI teachers as cultural agents responsible for sustaining local values amid global digital culture. It aims to analyze opportunities, challenges, and strategies applied by teachers at MAS Mujahidin Pontianak. A qualitative case study design was employed. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using an interactive model with triangulation for validity. Findings show that the digital era presents both challenges and opportunities for revitalizing local wisdom. Opportunities emerge through digital media use, integration of local values into Islamic education, and project-based P5RA learning. However, challenges include students’ low cultural literacy, dominance of global popular culture, and limited local learning resources. The study further indicates that preserving local wisdom depends on teachers’ ability to design contextual, collaborative, and reflective learning. Theoretically, it contributes to Islamic education discourse on local wisdom within the framework of hyperreality. Practically, it offers insights for developing adaptive Islamic education strategies that strengthen cultural identity in the digital age.